2015
DOI: 10.1155/2015/498254
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystallization, and Dielectric Behaviour of Lead Bismuth Titanate Borosilicate Glasses with Addition of 1% La2O3

Abstract: Lead bismuth titanate borosilicate glasses were prepared in the glass system 65[(Pb Bi 1− )⋅TiO 3 ]-34[2SiO 2 ⋅B 2 O 3 ]-1La 2 O 3 (0.0 ≤ ≤ 1.0) doped with one mole percent of La 2 O 3 via conventional melt quench method. The amorphous nature of glass samples in this glass system is confirmed by using X-ray diffraction (XRD) study. Differential thermal analysis (DTA) has been employed to determine the glass transition temperature, , as well as crystallization temperature, . DTA measurements were recorded in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Thus, the properties of produced glass ceramics are better than that of the parent glasses in many aspects. Numerous studies revealed that the structural, optical, and dielectric properties of various types of glassy compounds varied with the concentration of used additives [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the properties of produced glass ceramics are better than that of the parent glasses in many aspects. Numerous studies revealed that the structural, optical, and dielectric properties of various types of glassy compounds varied with the concentration of used additives [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Gautam et al investigated a new perovskite (Ba,Sr)TiO 3 borosilicate glassy system doped with La 2 O 3 in which they studied their structural and optical properties using various spectroscopy techniques [26,27]. Recently, Gautam et al reported numerous optical, and dielectric properties of different glass and glass ceramic compounds doped with different additives [19,28,29]. Kaur et al have reported the influence of modifiers strength on various physical, optical, structural, and mechanical properties of AO-SiO 2 -B 2 O 3 -La 2 O 3, (A = Mg, Ca, Sr, Ba) the glasses [30].…”
Section: Introductionmentioning
confidence: 99%
“…They also reported a spontaneous distortion within crystal grains of transparent PbTiO 3 GCs that precipitated in a glassy compound PbO-TiO 2 -Al 2 O 3 -SiO 2 . Literature showed various information are accessible on lead titanate glasses [27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Yadav et al investigated new perovskite glass and glass ceramic synthesis for high energy storage applications [13,14]. More recently, optical and electrical properties of (Pb x Bi 1-x ).TiO 3 borosilicate glass and glass ceramic systems were extensively reported by Gautam et al [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%